Subchronic Oral Toxicity Study of Decitabine in Combination With Tetrahydrouridine in CD-1 Mice. (March 2014) - Terse, Pramod; Engelke, Kory; Chan, Kenneth; Ling, Yonghua; Sharpnack, Douglas; Saunthararajah, Yogen; Covey, Joseph M.
Decitabine (5-aza-2′-deoxycytidine; DAC) in combination with tetrahydrouridine (THU) is a potential oral therapy for sickle cell disease and β-thalassemia. A study was conducted in mice to assess safety of this combination therapy using oral gavage of DAC and THU administered 1 hour prior to DAC on 2 consecutive days/week for up to 9 weeks followed by a 28-day recovery to support its clinical trials up to 9-week duration. Tetrahydrouridine, a competitive inhibitor of cytidine deaminase, was used in the combination to improve oral bioavailability of DAC. Doses were 167 mg/kg THU followed by 0, 0.2, 0.4, or 1.0 mg/kg DAC; THU vehicle followed by 1.0 mg/kg DAC; or vehicle alone. End points evaluated were clinical observations, body weights, food consumption, clinical pathology, gross/histopathology, bone marrow micronuclei, and toxicokinetics. There were no treatment-related effects noticed on body weight, food consumption, serum chemistry, or urinalysis parameters. Dose- and gender-dependent changes in plasma DAC levels were observed with a Cmax within 1 hour. At the 1 mg/kg dose tested, THU increased DAC plasma concentration (∼10-fold) as compared to DAC alone. Severe toxicity occurred in females receiving high-dose 1 mg/kg DAC + THU, requiring treatment discontinuation at week 5. Severity and incidence of microscopic findings increased in a dose-dependent fashion; findings included bone marrow hypocellularity (with corresponding hematologic changes and decreases in white blood cells, red blood cells, hemoglobin, hematocrit, reticulocytes, neutrophils, and lymphocytes), thymic/lymphoid depletion, intestinal epithelial apoptosis, and testicular degeneration. Bone marrow micronucleus analysis confirmed bone marrow cytotoxicity, suppression of erythropoiesis, and genotoxicity. Following the recovery period, a complete or trend toward resolution of these effects was observed. In conclusion, the combination therapy resulted in an increased sensitivity to DAC toxicity correlating with DAC plasma levels, and females are more sensitive compared to their male counterparts.